Pengaruh Nilai Perusahaan Tobin's Q, Price to Book Value (PBV), dan Price to Earnings Ratio (P/E), Terhadap Return On Equity (ROE) Pada Perusahaan Sektor Property and Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2024 - Agung Prihadianto; Fahriza Ananda Jonsa; Fajar Alwi Munawar; Jeny Ivana; K Pahotan Pasaribu; Mutiara Sari; Ranita Irawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of firm value, measured by Tobin's Q, Price to Book Value (PBV), and Price-to-Earnings Ratio (PIE), on Return on Equity (ROE). This research employs a quantitative approach with an associative research design, and the data used are secondary data. The data analysis method applied is panel data regression, which is processed using EViews version l3. The population of this study consists of property and real estate sector companies listed on the Indonesia Stock Exchange during the period 2Ol8-2O24. The results of this study indicate that Tobin's Q, PBV, and PIE have no significant effect on ROE, either partially or simultaneously.